Perbedaan Makna Modalitas Kamoshirenai Dan Osore Ga Aru Pada Kalimat Berita - Fahma Amalia Hanifa; Guswara, Yahya Adhar; Malia Rahmatika; Al Ghazali, Ghaza Gibran (Undiksha Press, 2024)
This research explores the diverse modalities within the structure of Japanese sentences, focusing on the modality of possibility known as